Surgical management of impalement injuries to the trunk of dogs: a multicentre retrospective study. (10th November 2017) - Matiasovic, M.; Halfacree, Z. J.; Moores, A.; Nelissen, P.; Woods, S.; Dean, B.; Chanoit, G.; Barnes, D. C.
Abstract : Objectives: To review a large series of dogs referred for treatment of traumatic impalement injuries to the thorax and/or abdomen and to report aetiologies, injury characteristics, management and long‐term outcomes. Materials and Methods: Previously collected data on dogs that were surgically treated for impalement injuries to the trunk at six veterinary specialist referral institutions in the UK over an 11‐year period were reviewed. Data included patient signalment, physiological variables, injury‐specific variables, diagnostic imaging reports, surgical procedures undertaken, duration of hospitalisation, antibiotic use, complications and outcomes. Data were reported with summary statistics. Results: Fifty‐four dogs were included. Impalement occurred most frequently on wooden objects (n=34), and the thoracic cavity was most commonly penetrated (n=37). Computed tomography was sensitive and specific to identifying wooden material in 64% and 88% of cases (n=11), respectively. Thoracotomy was performed in 56%, coeliotomy in 20% and a foreign body or its fragments were retrieved during surgery in 37% of the cases. Complications occurred in 19 dogs (35%), and of these, 68% were minor and 32% major. The survival rate for thoracotomy cases was 93% (n=30). Overall long‐term survival was 90%. Clinical Significance: Despite the often dramatic presentation of impalement injuries, the majority of patients treated in the specialist referral setting can achieve excellent outcomes. These injuries require thorough diagnostic imaging and interpretation before adequate surgical exploration and management, augmented by anaesthesia and critical care during the peri‐ and postoperative periods; therefore stable patients should be referred to centres able to provide this type of care.